Enhanced Recovery After Surgery for Patients Undergoing Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: A Systematic Review and Meta-Analysis - Mao, Feng; Huang, Zhenmin (Frontiers in Surgery, 2021)
Background: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a promising approach for the management of peritoneal carcinomatosis, but is associated with significant morbidity and prolonged hospital stay. Herein, we review the impact of Enhanced recovery after surgery (ERAS) protocol on length of stay (LOS) and early complications in patients undergoing CRS and HIPEC for peritoneal carcinomatosis. Methods: PubMed and Embase were searched for studies comparing ERAS protocol with control for CRS+HIPEC. Mean difference (MD) and risk ratios (RR) were calculated for LOS and complications respectively. Results: Six retrospective studies were included. Meta-analysis indicated statistically significant reduction in LOS with ERAS (MD: -2.82 95% CI: -3.79, -1.85 I2=29% p<0.00001). Our results demonstrated significantly reduced risk of Calvien Dindo grade III/IV complications with the use of ERAS protocol as compared to the control group (RR: 0.60 95% CI: 0.41, 0.87 I2=0% p=0.007). Pooled analysis of limited studies demonstrated no statistically significant difference in the risk of reoperation (RR: 1.04 95% CI: 0.54, 2.03 I2=50% p=0.90) readmission (RR: 0.55 95% CI: 0.21, 1.49 I2=0% p=0.24), acute kidney injury (RR: 0.55 95% CI: 0.28, 1.10 I2=0% p=0.09) or mortality (RR: 0.62 95% CI: 0.17, 2.26 I2=0% p=0.46) between the study groups. Conclusion: For CRS + HIPEC, ERAS is associated with significantly reduced LOS along with lower incidence of complications. Limited data suggest that use of ERAS protocol is not associated with increased readmission, reoperation, and mortality rates in these patients. There is a need for randomized controlled trials to corroborate the current evidence.